2020
DOI: 10.3389/fmicb.2020.00620
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Competition Amongst Deformed Wing Virus Genotypes in Naïve Australian Honeybees Provides Insight Into the Increasing Global Prevalence of Genotype B

Abstract: Honeybee colony deaths are often attributed to the ectoparasitic mite Varroa destructor and deformed wing virus (DWV), vectored by the mite. In the presence of V. destructor both main genotypes (DWV-A and DWV-B) have been correlated with colony loss. Studies show that DWV-B is the most prevalent genotype in the United Kingdom and Europe. More recently DWV-B has increased in prevalence in the United States. The increasing prevalence of DWV-B at the expense of DWV-A suggests that competition exists between the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
63
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 71 publications
14
63
3
Order By: Relevance
“…Interestingly, contrary to other studies [9,11,33], our samples were frequently co-infected with both master variants (Figures 2 and 3), potentially supporting the findings of Ryabov et al [35] that the different master variants are adapted to co-exist. While a recent experimental co-infection study showed that DWV-B replicated to higher levels than DWV-A in co-infections [36], and the vast majority of our samples contained more DWV-A reads than DWV-B, suggesting a lack of any strong competitive exclusion in this population. This was a similar finding as in the experimental infection study by Tehel et al [37] in which DWV-A replicated to slightly higher levels than DWV-B when co-infected.…”
Section: Discussioncontrasting
confidence: 55%
“…Interestingly, contrary to other studies [9,11,33], our samples were frequently co-infected with both master variants (Figures 2 and 3), potentially supporting the findings of Ryabov et al [35] that the different master variants are adapted to co-exist. While a recent experimental co-infection study showed that DWV-B replicated to higher levels than DWV-A in co-infections [36], and the vast majority of our samples contained more DWV-A reads than DWV-B, suggesting a lack of any strong competitive exclusion in this population. This was a similar finding as in the experimental infection study by Tehel et al [37] in which DWV-A replicated to slightly higher levels than DWV-B when co-infected.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, the type of mite-transferred viruses infecting the honey bee populations may influence infestation levels, allowing for or compromising survival. Differences in the virulence of the various deformed wing virus types [ 122 ], for instance, may have a direct effect on the number of mites that can be tolerated by the colony [ 123 , 124 ]. This survival threshold can also be influenced by the haplotype of the mite [ 125 ].…”
Section: Introductionmentioning
confidence: 99%
“…This condition can hardly be reproduced in common beekeeping conditions. In Wales, the involvement of viruses in colony survival is hypothesized via the superinfection exclusion of the virulent variant DWV-A by the less virulent variant DWV-B [ 122 , 205 , 206 ]. However, other results suggest a higher virulence of DWV-B when compared to DWV-A [ 207 , 208 ].…”
Section: Introductionmentioning
confidence: 99%
“…Africanised bees are also resistant to varroa mites, and despite the mite’s presence since the 1970s and 1980s, Brazil remains unique in that DWV-A remains the dominant genotype throughout the country, with DWV-B dominating in only one of 26 colonies studied [ 16 ]. This is unexpected, since under both controlled [ 20 , 21 ] and natural field conditions [ 9 , 10 ], DWV-B outcompetes and replaces DWV-A. This competition explains why there is no significant difference (χ 2 = 3.3, p = 0.07) between the number of DWV-A- or DWV-B-dominant colonies between the UK [ 10 ] and South Africa, which have both been infested with varroa mites for over 30 years.…”
mentioning
confidence: 99%